Fluorescence in the study of steroid metabolism - Ahonen, Jari (2020)
This thesis begins with a literature review that presents the basics of the fluorescence phenomenon and fluorescence microscopy. The literature on cellular cholesterol composition and cholesterol transport mechanisms is extensively studied. Thereafter, the fluorescent steroid-based molecules designed to identify cholesterol and cholesteryl esters suitable for use in living cells are covered. The literature review ends an overview of other applications for the use of fluorescent probes, for example in cell biology.